Exploring the victorian craze over the fear of cats.
The EU-funded DISEASES project has been exploring how the Victorians diagnosed, understood and dealt with many of the phenomena related to stress and overload that characterise today's modern globalised society. One intriguing discovery has been on the Victorian emphasis on phobias, particularly ailurophobia-the fear of cats.